Kualitas Organoleptik Kue Bugis Hitam Berbahan Dasar Tepung Kacang Gude Sebagai Substitusi Tepung Ketan Hitam - Sudiarta, Ngakan Putu; Prasanti, Kadek Dita (JURNAL GASTRONOMI INDONESIA, 2024)
This study explores the utilization of pigeon pea flour in Bugis cake production and its evaluation through organoleptic testing. Pigeon pea is recognized for its high protein and carbohydrate content. The research incorporates three samples: A (100% pigeon pea flour), B (1:2 ratio of glutinous rice flour to pigeon pea flour), and C (2:3 ratio of glutinous rice flour to pigeon pea flour). The primary objective is to assess the quality of Bugis cakes made using pigeon pea flour. Data collection methods encompass experimentation, organoleptic testing, panelists, questionnaires, and Likert scales. Qualitative descriptive analysis is employed for data analysis. The organoleptic testing results, evaluated using the Likert scale, indicate that sample A achieves an average score of 65% ("good"), sample B scores 81% ("very good"), and sample C scores 89% ("very good"). These findings underscore the potential of pigeon pea flour to enhance the quality of Bugis cakes. In the context of this research, pigeon pea flour plays a pivotal role as an alternative raw material that positively influences the organoleptic characteristics of Bugis cakes.